The Global Water Crisis: Water Diplomacy as an Effort to Avoid Conflict Between Countries - Judijanto, Loso; Fadhilah, Nurul (Synergisia, 2025)
The global water crisis is increasingly worrisome, especially in regions that rely on transboundary water resources such as the Middle East, Sub-Saharan Africa, South Asia, and Southeast Asia. Competition for access to clean water has the potential to trigger conflict, but it can also be an opportunity to build cooperation between countries through water diplomacy. This study aims to analyze the dynamics of water diplomacy in the midst of a global water crisis and identify the factors that influence its success and failure. The research method used is qualitative with a descriptive-analytical approach. Data were collected through literature studies from scientific journals, international organization reports, and policy documents, then analyzed using content analysis techniques and comparative analysis between regions. The results show that areas with strong cooperation mechanisms and international agreements, such as the Niger River basin, tend to be better able to manage potential conflicts. In contrast, tensions are rising in regions such as the Indus River (India–Pakistan) and the Nile River (Egypt–Ethiopia), where the uniliteral approach is still dominant. Water diplomacy has proven effective if it is supported by a clear legal framework, political commitment, and the mediating role of international organizations. Implicitly, countries need to strengthen water diplomacy policies as part of their security and sustainable development strategies, as well as encourage inclusive regional cooperation for transboundary water resources management.